Pseudomonas syringae pv. actinidiae Type III Effectors Localized at Multiple Cellular Compartments Activate or Suppress Innate Immune Responses in Nicotiana benthamiana - Choi, Sera; Jayaraman, Jay; Segonzac, Cécile; Park, Hye-Jee; Park, Hanbi; Han, Sang-Wook; Sohn, Kee Hoon (Frontiers in Plant Science, 2017)
Bacterial phytopathogen type III secreted (T3S) effectors have been strongly implicated in altering the interaction of pathogens with host plants. Therefore, it is useful to characterize the whole effector repertoire of a pathogen to understand the interplay of effectors in plants. Pseudomonas syringae pv. actinidiae is a causal agent of kiwifruit canker disease. In this study, we generated an Agrobacterium-mediated transient expression library of YFP-tagged T3S effectors from two strains of Psa, Psa-NZ V13 and Psa-NZ LV5, in order to gain insight into their mode of action in N. tabacum and N. benthamiana. Determining the subcellular localization of effectors gives an indication of the possible host targets of effectors. A confocal microscopy assay detecting YFP-tagged Psa effectors revealed that the nucleus, cytoplasm and cell periphery are major targets of Psa effectors. Agrobacterium-mediated transient expression of multiple Psa effectors induced HR-like cell death (HCD) in Nicotiana spp., suggesting that multiple Psa effectors may be recognized by Nicotiana spp.. Virus-induced gene silencing (VIGS) of several known plant immune regulators, EDS1, NDR1 or SGT1 specified the requirement of SGT1 in HCD induced by several Psa effectors in N. benthamiana. In addition, the suppression activity of Psa effectors on HCD-inducing proteins and PTI was assessed. Psa effectors showed differential suppression activities on each HCD inducer or PTI. Taken together, our Psa effector repertoire analysis highlights the great diversity of T3S effector functions in planta.